Études des propriétés physiques de LiNbO3 pur et dopé à l’aide de la théorie de la fonctionnelle de la densité - Ait brahim Imane (Faculté des Sciences de Rabat, 2021)
This thesis presents a theoretical study to approve an improvement of the properties of lithium niobate (LN) by doping and by strain effect, by the density functional theory (DFT), implemented in the WIEN2k_16 package. The exchange-correlation potential is treated with the GGA-PBE, TB-MBJ and HSE06 approximations. The effect of uniaxial and biaxial compressive and tensile strain on structural, electronic and optical properties are investigated in detail, thermoelectric properties are also determined using semi-classical Boltzmann theory, implemented in the BoltzTraP code, the results found prove that the deformed structures carry an improvement of the optical properties in the visible and UV zone. The effect of doping by magnetic elements (Cr and Fe) on the structural, magnetic and electronic properties have been studied, and the material doped by different percentages exhibits a change from semi-conductor behavior to semi-metal behavior, which is favorable for spintronic applications, the thermodynamic properties were calculated by the quasi-harmonic Debye model implemented in the GIBBS program. The effects of doping by non-magnetic elements (S, Se, Te and Cs) on the electronic, optical and thermoelectric properties have also been treated. It appears that the gap energy is considerably reduced with the increase in the concentration of dopants, useful for thermoelectric, optoelectronic and photovoltaic applications.
Study of physical properties of pure and doped LiNbO3 using density functional theory.
Keywords: ab; initio; GGA; mBJ; DFT; photovoltaïque; spintronique; thermoélectrique; thermodynamique; dopage; contrainte uniaxiale/biaxiale.; Sciences des matériaux